Management of spot blotch using fungicidal combinations in wheat (Triticum aestivum) - KUMAR, UDAY; AZAD, C S; KUMAR, AMARENDRA; KUMAR, SANJEEV; BARANWAL, DEEPAK KUMAR (The Indian Journal of Agricultural Sciences, 2025)
Spot blotch is a major constraint to wheat (Triticum aestivum L.) production in the Eastern Gangetic Plains (EGP) of India, where wheat cultivars express moderate resistance to susceptible reaction. Limited information available on yield penalties under varying disease severities. The present study was carried out during winter (rabi) seasons of 2021–22 and 2022–23 at Bihar Agricultural University, Sabour, Bihar to assess the efficacy of selected fungicidal combinations against wheat spot blotch under in vitro and in vivo conditions. A total of eight fungicidal combinations were evaluated, including tebuconazole 50% + trifloxystrobin 25% wg, propiconazole 13.9% + difenoconazole 13.9% ec, azoxystrobin 12.5% + tebuconazole 12.5% sc, picoxystrobin 7.05% + propiconazole 11.7% wsc, kresoxim-methyl 44.3% sc, propiconazole 25% ec, tebuconazole 22.9% ec, and mancozeb 75% wp, each tested at four concentration levels. In vitro activity was quantified using radial mycelial growth inhibition assays, while in vivo efficacy was examined through field trials conducted in a randomized block design. In vitro results showed complete fungal mycelial growth inhibition by all four combinations at 100 ppm, while at 75 ppm, tebuconazole 50% + trifloxystrobin 25% wg achieved the highest inhibition (91.84%). Field trials conducted over two years revealed that tebuconazole 50% + trifloxystrobin 25% wg at 1 g/Lwas the most effective in reducing disease severity, with the lowest infected plant, disease incidence and percent disease index. This treatment has also achieved maximum disease reduction (81.69% and 80.96%) resulting 28.91% and 27.46% yield increase over control during 2021–22 and 2022–23, respectively. Hence, it is concluded that, tebuconazole 50% + trifloxystrobin 25% wg belonging to two different chemical family group with broad mode of actions, is highly effective for managing spot blotch in wheat.